Solar collector storage tank - Nur Liyana, Abdul Rahim (2013)
Solar collector storage tank is water tank used to store hot water for space heating or domestic use. The main purpose of this project is to design and fabricate storage tank for evacuated tube solar collector and to determine the overall heat loss of the storage tank and the period of heat energy storage after sunset. Two types of insulator are used for testing the respectively such as polyurethane and woolen coat. This is due to low thermal conductivity of polyurethane and sheep wool of 0.03 W/m.K and 0.039 W/m.K compared to insulator which is many orders higher. The experiment consists to two types of fluid which are distilled water and nanofluid of silicon oxide (SiO). In this experiment, the systems are divided into two types which are without control system and with control system. The results obtained show that to the nanofluid using silicon oxide (SiO) with control system is the best result compared distilled water. It has shown the result of nanofluid achieved higher temperature of 86.7 and with different temperature of 47.52 %. The investigation for distilled water shows, the storage temperature with control system is higher than without control system with different 6.68 %.